Inferior mesenteric artery skeletization with para-aortic lymphadenectomy in the treatment of left-sided colon cancer - P. V. Tsarkov; A. Yu. Kravchenko; I. A. Tulina; B. N. Bashankayev; O. Yu. Samofalova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. Development and efficacy evaluation of oncologically proved and safe surgical methods for various locations and stages of left-sided colon cancer.Material and methods. Overall 59 patients with left-sided colon cancer were selected from February, 2008 to May, 2011. All patients underwent bowel resection in different volume with para-aortic lymph node dissection and skeletization of inferior mesenteric artery (detailed description of the procedure is presented): 11 left-side hemycolectomies, 14 partial resections of the left colon, 13 distal and 21 segmentary resection of sigmoid colon were executed.Results. The highest duration of operation (250,9±71,5 min) and volume of intraoperative blood loss (745,4±737,0 ml) was observed at left-side hemicolectomy, duration of other interventions did not exceed 3 h, and the blood loss – was less than 250 ml. Postoperative complications developed in 9 patients. The mean number of investigated lymph nodes in resected speciemens was 26,4±18,2. Metastatic involvement was most frequent in paracolic lymph nodes, affected apical lymph nodes are revealed in 2 cases. Cumulative three-year survival rate was 93%.Conclusion. Applied technique of inferior mesenteric artery skeletization allows to carry out extensive para-aortic lymph node dissection and to keep supplying vessels. This allows to decrease considerably the number of left-side hemicolectomies for segmentary resections. Presented interventions are safe from the point of postoperative morbidity and are characterized by good oncologic results.